The playful component in teaching Arabic as a foreign language - Lucena Romero, Miguel Ángel (Anaquel de Estudios Árabes, 2021)
In the field of teaching foreign languages, the application of recreational activities in the classroom has become a subject of interest for teachers and researchers in recent years. In this paper, we focus on the theoretical aspects that most influence the learning of foreign languages ​​through the playful component and especially the case of Arabic language. Likewise, in this work we present a series of didactic games that Arabic language teachers can use, above all, to improve oral expression, to strengthen writing skills and to promote motivation and active participation of students.